Optimization of Pregnant Women's Knowledge about Nausea, Vomiting and the Use of Ginger Honey Drink to Reduce Nausea, Vomiting - Erma Retnaningtyas; Tri Hastuti; Yuliana Elma; Henderiana Kililily; Dwi Purwaningsih; Iriani Winoto; Hendrika Lawalata; Salmawaty; Elbina Sihombing (Journal of Community Engagement in Health, 2024)
Nausea and vomiting that occurs in the first trimester of pregnancy is caused by increased levels of the hormones Estrogen and Human Chorionic Gonadotropin (HCG) in the serum from the placenta. Nausea, vomiting often occurs when you wake up in the morning, which is also called morning sickness. The aim of this community service is to optimize pregnant women's knowledge about the benefits of ginger-honey drinks to reduce nausea and vomiting in pregnant women in the first trimester. This activity is carried out by providing education about nausea and vomiting in the first trimester of pregnancy by giving a pre-test questionnaire about nausea and vomiting before being given counseling and post test questionnaire about nausea and vomiting after being given counseling. Then they carried out a demonstration on making Honey Ginger leaf drink and immediately distributed it for pregnant women to drink. This counseling was carried out at the Mawar posyandu in the working area of the Karang Indah Community Health Center, Merauke district, which was attended by 23 pregnant women. The results of the counseling before the counseling was given were 13 pregnant women (57%) with good knowledge and after the activity there was an increase in knowledge to 22 pregnant women (96%) with good knowledge. It is hoped that there will be more emphasis on treating nausea and vomiting by utilizing the natural wealth around us, namely ginger and honey.